Nursing Interventions for Head and Neck Cancer Patients That Promote Embracement in the Operating Room/Surgery Unit: A Near-Empty Scoping Review - Carla Sofia Ramos Cruz; Cristina Lavareda Baixinho; Rafael A. Bernardes; Óscar Ramos Ferreira (MDPI AG, 2022)
Head and neck tumours are the fifth leading cause of cancer deaths worldwide. They are hostile invasive neoplastic diseases that negatively impact individuals' functionality. The aim of this study was to map the nursing interventions to be carried out with head and neck cancer patients in preoperative nursing consultations. Given the study's aim, a scoping review was chosen based on the principles advocated by the Joanna Briggs Institute and using the CINAHL and Medline databases. The review was conducted in April and May 2021. Of the 56 articles obtained, only 1 met the inclusion criteria, indicating a gap in studies about head and neck cancer patients. Preoperative nursing consultations allow patients and family members to ask questions and voice concerns. The nursing intervention identified by the review included interviews, in which nurses explain the concepts related to the diagnosis, the procedures involved in the surgery, and the inherent consequences. Flyers containing images and photos can be used to facilitate interpretation.